(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The great social significance of ear, nose and throat diseases is determined by their high incidence in childhood. The prevalence of chronic otorhinolaryngological pathology in children in Uzbekistan ranges from 181.9 to 465.0 per 1000 children, with adenotonsillar pathology occupying a leading position.